A model for L1 grammatical attrition. (April 2020) - Hicks, Glyn; Domínguez, Laura
This article proposes a formal model of the human language faculty that accommodates the possibility of 'attrition' (modification or loss) of morphosyntactic properties in a first language. Modeling L1 grammatical attrition entails a quite fundamental paradox: if the structure of the language faculty in principle allows for attrition of morphosyntax, why is it apparently so heavily constrained and rarely attested? We demonstrate that the attrition paradox can be resolved with a model that integrates a formally explicit generative grammar (eschewing classical parameters in favor of functional feature assemblies; see Chomsky, 2000, 2001) into a generalized model of language acquisition that decouples linguistic input from acquisitional intake (following Lidz and Gagliardi, 2015). This implementation makes specific predictions about the input and intake conditions that favor and disfavor L1 attrition. We explore these predictions for one of the most widely studied areas of attrition, namely the realization of pronominals.